SUBTAINABILITY OF FAMILY VALUES THROUGHOUT THE GENERATIONS AS VIEVED BY THE BACHELOR PROGRAM STUDENTS - Ilisko, Dzintra; Kravale - Paulina, Marite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The meaning of a term “family” differs from one group of people to another and changes over time. The definition has important political, economic, social and ecological consequences, often determining family members’ roles, rights and obligations. Maintaining and fostering the value of strong families ensures a sustainable development of a country. Strong family with stable values is an excellent instrument of resistance and adaptation to the external world and pressures. The study presents the survey done on bachelor program students’ view on sustainability and how they maintain family values throughout the generations. This helps to build bridges over the traditional and the modernity aspects that emerge in the society’s contemporary understanding of a family as a structural and spiritual unit. The methods of the research employed are the following: the study presents a qualitative research that comprises the content analyses of fifty six essays on a perception of a family by the bachelor programme students from one regional university of Latvia. The data is supported by the focus group interviews carried out with the full time students that are employed in the educational courses „Family pedagogy” and „Social pedagogy” (n = 111).